The effect of brain vitalization activity on dementia incidence in elderly at Budi Luhur Nursing Home of Yogyakarta, Kasongan, Bantul - Firstyono Miftahul Aziz; Suratini Suratini (International Journal of Health Science and Technology, 2020)
For some people, dementia is considered as a disease that is common in elderly, regardless the impact of dementia. Taking care for the elderly with dementia brings stress for the family. It can cause and increase the family burden. Brain vitalization gymnastics is one of the methods to improve memory. The study aims to investigate the effect of brain vitalization activity on dementia incidence in elderly at Budi Luhur Nursing Home of Yogyakarta. The study used Quasi Experimental with Pretest-Posttest control group and randomized sampling system. The samples were taken randomly as many as 26 respondents and were divided into two groups namely 13 respondents of experimental group and 13 respondents of control group. The statistical test used Wilcoxon Match Pairs Test. The result showed that Wilcoxon Match pairs test obtained p value 0,003, which is smaller than 0,005. There is an effect of brain vitalization activity on dementia incidence in elderly at Budi Luhur Nursing Home of Yogyakarta